IMPORTANCE OF SECONDARY MARKET INTERNATIONAL FOREIGN DEBT SECURITIES: THEIR CONTRIBUTION TO INTERNATIONAL FINANCE - Villamonte Blas, Ricardo Norberto (2013)
The best contribution academically can provide financial events that contributed to the development of international finance is to study them in depth so that their treatments and outcomes allow experts and stakeholders to have a better understanding of its evolution , characteristics and importance . The International Securities Secondary Market of External Debt (MSDE) is typified as a very unique market, defining it as a bilateral trading market with special features, which has had a crucial role. Although its contribution was marginal compared to the total amount of debt then 59 billion dollars were converted versus 600 billion dollars in debt, thanks to this market. First, they constitute new financial arrangements that under the market mechanism, allowed to alleviate or partially solve the plight of the financial statements of its principal and secondary actors, allowed to clarify and recognize the creditors that the market value was the basis for a negotiation that would serve as an important contribution to the partial solution for them and for borrowers of foreign debt which came to be regarded as an outdated financial product.